Collagen-based scaffolds enriched with glycosaminoglycans isolated from skin of Salmo salar fish. (September 2017) - Kaczmarek, Beata; Sionkowska, Alina; Osyczka, Anna Maria
Abstract: In this study both collagen and glycosaminoglycans were isolated from biodegradable waste. Namely collagen was isolated from rat tail tendons and glycosaminoglycans (GAGs) from fish skin. Porous materials were then obtained based on the isolated collagen with 1 or 5% addition of GAGs by freeze-drying process. The scaffolds were studied by infrared spectroscopy, mechanical testing and examined for the porosity and density. The scaffolds structure was observed by scanning electron microscope. The adhesion and proliferation of human osteosarcoma SaOS-2 cells was examined on prepared scaffolds to assess their biocompability. The results showed that the addition of glycosaminoglycans improves the properties of collagen-based scaffolds. Mechanical strength was increased by GAGs addition as well as the porosity of studied materials. Each scaffold with and without GAGs displayed porous structure with interconnected regular shaped pores. The attachment of cells was better for pure collagen scaffold, however, GAGs additive promoted the cells proliferation on the scaffold.